Implikasi Puasa Senin Kamis Bagi Akhlak Siswa Di MA Darussalam Deru Bojonegoro - Miftah, Zaini; Burhanuddin, Hamam; Lastutik, Sri (At-Tuhfah : Jurnal Studi Keislaman, 2023)
This research aims to determine the implications of Monday and Thursday fasting for the morals of students at MA Darussalam Deru. The background to which this research was conducted is in today's era, most Muslims today are very few who seriously, consistently and consistently uphold the teachings of Allah and the Messenger. -His. Fasting on Mondays and Thursdays is a form of worship that was highly recommended by Rasulullah SAW. Monday and Thursday fasting has the meaning of sunnah fasting which is done on Thursdays, and the Prophet liked to fast on both days. For the reason that on Mondays and Thursdays all the deeds of Adam's children are reported (raised), and he hopes that, when his deeds are raised before Allah while fasting, the method used in this research is descriptive qualitative with data collection techniques of observation, in-depth interviews and triangulation data. The results of research on the morals of Madrasah Aliyah Darussalam students who regularly perform sunnah fasting on Mondays and Thursdays have an increased spiritual spirit, so that they become more disciplined, patient, trustworthy, honest, have good attitudes towards fellow students, are patient, more disciplined and of course have more noble character. The implications of sunnah fasting on Mondays and Thursdays can shape female students' morals through several aspects, namely spiritual aspects and physical aspects. Through the spiritual aspect: by fasting the sunnah can increase devotion to Allah, have fear of, and all actions that are done with the pleasure of Allah, they fast to get closer to and carry out the Sunnah of the Prophet. Next is the physical aspect, with this, after fasting, female students feel more enthusiastic, active and healthy.